2010
DOI: 10.2139/ssrn.1721936
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Science in the Patent System: An Analysis of the Semiconductor Technology

Abstract: Die Dis cus si on Pape rs die nen einer mög lichst schnel len Ver brei tung von neue ren For schungs arbei ten des ZEW. Die Bei trä ge lie gen in allei ni ger Ver ant wor tung der Auto ren und stel len nicht not wen di ger wei se die Mei nung des ZEW dar.Dis cus si on Papers are inten ded to make results of ZEW research prompt ly avai la ble to other eco no mists in order to encou ra ge dis cus si on and sug gesti ons for revi si ons. The aut hors are sole ly respon si ble for the con tents which do not neces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…This line of research has also outlined how scientific openness is a critical element of a firm's IP strategy to affect prior art. Strategic scientific disclosures, namely defensive publishing, can exert a major impact on patent races (e. g. Bar, 2006;Della Malva and Hussinger, 2012;Johnson, 2014; 1 Most of the studies that were snowballed from the initial sample included, in their full text, at least one of the keywords reported in Table 1. However, these studies were not identified by our query since WoS searches do not extend to the full text of publications.…”
Section: An Overview Of Extant Researchmentioning
confidence: 99%
“…This line of research has also outlined how scientific openness is a critical element of a firm's IP strategy to affect prior art. Strategic scientific disclosures, namely defensive publishing, can exert a major impact on patent races (e. g. Bar, 2006;Della Malva and Hussinger, 2012;Johnson, 2014; 1 Most of the studies that were snowballed from the initial sample included, in their full text, at least one of the keywords reported in Table 1. However, these studies were not identified by our query since WoS searches do not extend to the full text of publications.…”
Section: An Overview Of Extant Researchmentioning
confidence: 99%
“…Among the 25 firms with the highest number of declarations related to standards released by the European Telecommunications Standards Institute is Siemens the only German firm (Bekkers et al, 2020a). patents of competitors, without incurring cost of acquiring formal intellectual property measures (Barrett, 2002;Gans et al, 2017;Hayter and Link, 2018;Johnson, 2014;Della Malva and Hussinger, 2012;Pénin, 2007). Publishing can also help to commercialize innovations, as they can signal the effectiveness of products to potential users (Azoulay, 2002;Hicks, 1995;Rafols et al, 2014), or encourage regulators to approve products (Penders and Nelis, 2011).…”
Section: Publishingmentioning
confidence: 99%
“…Recent studies analyzed its impact on innovation performance Henderson, 1998, Jong andSlavova, 2014;Li et al, 2015), firm valuation (Arora et al, 2018;Pellens and Della Malva, 2018;Simeth and Cincera, 2016), and economic competitors (Della Malva and Hussinger, 2012). The same is the case for the development of standards.…”
Section: Introductionmentioning
confidence: 99%
“…First, the combination of patents and scientific documents which typically cover rather basic technological advances that need to be combined with applied technologies to be novelty challenging (Della Malva and Hussinger, 2010) are Y-type citations. Second, patent families that threaten the novelty of patent applications are cited as Ys.…”
Section: Guellec Et Al 2008) Prior Research Has Shown That Patentsmentioning
confidence: 99%